Pobreza multidimensional para Bogotá. Bajo la lupa del entorno: una mirada espacial. - Hurtado Beltrán, Johanna Paola. (Escuela Colombiana de Ingeniería Julio Garavito, 2014)
This work proposes to broaden the field of vision of the Multidimensional Poverty Index (MPI), by including in the measurement an additional dimension that evaluated the housing environment in Bogotá, with the use of quality of life surveys (LCA) 2003 and 2007 and the multipurpose survey of Bogotá (EMB) 2011. With this intention, two types of exercises are carried out: the first includes some indicators of access to public facilities, private development and environmental quality for the surveys; in the second, the surveys are compared with environmental variables present in the three surveys. The remaining dimensions remain the same as those specified by the DANE for the official calculation.

Este trabajo propone ampliar el campo de visión del Índice de Pobreza Multidimensional (IPM), al incluir en la medición una dimensión adicional que evalué el entorno de la vivienda en Bogotá, con el uso de las encuestas de calidad de vida (ECV) 2003 y 2007 y la encuesta multipropósito de Bogotá (EMB) 2011. Con esta intensión se realizan dos tipos de ejercicios: el primero incluye algunos indicadores de acceso a equipamientos públicos, de desarrollo privado y de calidad ambiental para las encuestas; en el segundo se compara las encuestas con variables de entorno presentes en las tres encuestas. Las dimensiones restantes se mantienen igual a las especificadas por el DANE para el cálculo oficial.
Keywords: Pobreza multidimensional; Entorno de vivienda; Políticas públicas; Multidimensional poverty; Public politics; Housing environment